THE INFLUENCE OF PRINCIPAL LEADERSHIP AND INTERNAL COMMUNICATION ON TEACHER PERFORMANCE AT SMK NEGERI 1 MAJALENGKA - M Oktarifan Agung Nugroho; Dian Indiyati (PT. Jurnal Center Indonesia Publisher, 2026)
The background of this research is based on the need to improve the quality of education and the demand for teacher professionalism in facing the dynamic challenges of school management. At SMK Negeri 1 Majalengka, the effectiveness of the principal’s leadership and the quality of internal communication are considered two important factors that may play a strategic role in enhancing teacher performance. These conditions highlight the need for empirical analysis to determine the extent to which these two aspects contribute to the achievement of teacher performance. This study aims to examine the description of principal leadership, internal communication, and teacher performance at SMK Negeri 1 Majalengka, as well as to analyze the influence of principal leadership on teacher performance, the influence of internal communication on teacher performance, and the influence of both variables on teacher performance. Thus, this research not only describes the actual conditions but also tests the relationships between the variables under study. The research employed descriptive and correlational methods. The study population consisted of all 141 teachers at SMK Negeri 1 Majalengka. The sample was determined using the Slovin formula, resulting in 104 respondents selected through proportional sampling. The research instrument was a questionnaire that had undergone validity and reliability testing. Data analysis was carried out to determine the strength of the relationships between variables and to test the research hypotheses. The results indicate that principal leadership falls into the very competent category, internal communication is carried out high effectively, and teacher performance is categorized as very high. Correlational analysis findings show that principal leadership (X₁) has a significant influence on teacher performance, and internal communication (X₂) also has a significant influence on teacher performance. Simultaneously, both independent variables have a meaningful effect on improving teacher performance at SMK Negeri 1 Majalengka. The implications of this study show that improving teacher performance can be achieved through strengthening principal leadership and implementing effective internal communication. Therefore, schools are advised to continuously build open and collaborative communication patterns and optimize leadership roles in providing direction, support, and exemplary behavior for teachers.